2011
DOI: 10.1063/1.3659282
|View full text |Cite
|
Sign up to set email alerts
|

Refinement of the theory for extracting cell dielectric properties from dielectrophoresis and electrorotation experiments

Abstract: A modified theory is proposed for extracting cell dielectric properties from the peak frequency measurement of electrorotation (ER) and the crossover frequency measurement of dielectrophoresis (DEP). Current theory in the literature is based on the low frequency (DC) approximations for the equivalent cell permittivity and conductivity, which are valid when the measurements are performed in a medium with conductivity less than 1 mS=m. The present theory extracts the cell properties through optimizing an express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 30 publications
1
44
0
Order By: Relevance
“…6 Linear fitting of (f ⋅ r) against σ m , based on data from Fig. 4c and the formula in [26], predicts cell membrane effective capacitance well within our suggested range, verifying the accuracy of our fitting procedure most severe situation (only 10% sucrose). Sufficiently high viability (87%) was achieved for hippocampal cells after short-term (30 min) exposures to sucrose, compared with the control sample (88%) in pure cell culture media.…”
Section: Property Determination For Glial Cellsmentioning
confidence: 89%
See 3 more Smart Citations
“…6 Linear fitting of (f ⋅ r) against σ m , based on data from Fig. 4c and the formula in [26], predicts cell membrane effective capacitance well within our suggested range, verifying the accuracy of our fitting procedure most severe situation (only 10% sucrose). Sufficiently high viability (87%) was achieved for hippocampal cells after short-term (30 min) exposures to sucrose, compared with the control sample (88%) in pure cell culture media.…”
Section: Property Determination For Glial Cellsmentioning
confidence: 89%
“…From Table 3, most of the conductivity of the suspension mixture is magnitudes higher than that of DEP buffers previously used [11,14,21,24,26,27] because of the addition of cell culture media, which compromises the validity of the lowfrequency approximation, as mentioned earlier. In order to ensure the survival of cells in these suspension mixtures, we investigated the viability of hippocampal cells in the Fig.…”
Section: Property Determination For Glial Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2) leads to an accurate measurement of the membrane capacitance. 16 Labeed et al 17 have recently reported that the neurogenic potential of human neural stem/progenitor cell populations can be discriminated by their f xo and derived C m values. On the basis of the efficient DEP-based cell separations reported here, the same conclusion may be reached regarding discrimination between stages of C2C12 myoblast cell differentiation.…”
Section: -1058/2012/6(3)/034113/16/$3000mentioning
confidence: 99%